2017
DOI: 10.1080/17483107.2017.1389998
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning from virtual reality to natural environments in individuals with Duchenne muscular dystrophy

Abstract: For individuals with DMD, conducting a coincidence timing task in a virtual environment facilitated transfer to the real environment. However, we emphasize that a task practiced in a virtual environment should have higher rates of difficulties than a task practiced in a real environment. IMPLICATIONS FOR REHABILITATION Virtual environments can be used to promote improved performance in ?real-world? environments. Virtual environments offer the opportunity to create paradigms similar ?real-life? tasks, however t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 44 publications
1
36
1
1
Order By: Relevance
“…As a result, the engagement only maintained the good performance of the TD group. Other studies used a motor learning protocol and only used the coincident timing as a laboratory task, which increased the difficulty of engagement and made it impossible to practice for a long period of time 20,31. However, the task proposed by the MoveHero software provides a greater engagement, probably due to the number of spheres, songs used, and the existence of an avatar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the engagement only maintained the good performance of the TD group. Other studies used a motor learning protocol and only used the coincident timing as a laboratory task, which increased the difficulty of engagement and made it impossible to practice for a long period of time 20,31. However, the task proposed by the MoveHero software provides a greater engagement, probably due to the number of spheres, songs used, and the existence of an avatar.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of MoveHero (virtual task), the timing error was defined as the difference between the time the ball hit the target sphere and the time the individual managed to hit the target with the avatar’s hand. As used by de Mello Monteiro et al,20,21 Quadrado et al,31 and Bezerra et al,32 the error time in milliseconds can be used to analyze the constant error (CE), which evaluates the directional tendency of the movement; the absolute error (AE), which demonstrates the accuracy of the movement; and the variable error (VE), which identifies the accuracy of the movement (for details about these errors, see de Mello Monteiro et al21). CE, AE, and VE were used as dependent variables for both the coincident timing task and MoveHero.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…A relatively small number of studies have explored motor skill acquisition and transfer from virtual to real environments in healthy and neurologically impaired populations. Several studies used a simple coincidence timing task in which participants intercepted a falling virtual object by either pressing a key on computer (physical task) or making a hand movement tracked by webcam (virtual task) [6769]. In adolescents with CP, older adults and healthy controls, practice in the VE did not transfer to improved performance of the real-world task [68, 69].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a study in healthy subjects demonstrated that skill acquisition of the sequential motor learning occurs at the same rate in both VE and conventional screen environments, while the transfer of motor skills was not observed from VE to the screen environment 15 . Another study reported that skill acquisition in individuals with the neuromuscular diseases transferred from VEs to REs 19 . In contrast, motor learning and motor performance did not transfer from VEs to REs in older adults and individuals with neuromuscular diseases 18,20,21 .…”
Section: Introductionmentioning
confidence: 99%